1993
DOI: 10.1073/pnas.90.5.1927
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric and Edman sequencing of lipocortin I isolated by two-dimensional SDS/PAGE of human melanoma lysates.

Abstract: We have integrated preparative twodimensional polyacrylamide gel electrophoresis with highperformance tandem mass spectrometry and Edman degradation. By using this approach, we have isolated and identified, by partial sequencing, a human melanoma protein (34 kDa, pI 6.4) as lipocortin I. To our knowledge, this protein was not previously known to be associated with melanoma cells. The identity of the protein was confirmed by two-dimensional immunoblot analysis. High-energy colsion-induced dissociation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…BLAST searches for sequence similarity of the proteins in the GenBank data bases showed that the sequence of the 37-kDa band was Ͼ80% similar to a sequence beginning with the 13th residue of a leukocyte calcium binding protein, annexin I. Native annexin I is known to be blocked at the N terminus (8). The identity of annexin I was further confirmed in immunoblots by using a commercially available mouse mAb against bovine annexin I.…”
Section: A Very Small Fraction Of the Proteins From Whole Bovine Lungmentioning
confidence: 81%
See 1 more Smart Citation
“…BLAST searches for sequence similarity of the proteins in the GenBank data bases showed that the sequence of the 37-kDa band was Ͼ80% similar to a sequence beginning with the 13th residue of a leukocyte calcium binding protein, annexin I. Native annexin I is known to be blocked at the N terminus (8). The identity of annexin I was further confirmed in immunoblots by using a commercially available mouse mAb against bovine annexin I.…”
Section: A Very Small Fraction Of the Proteins From Whole Bovine Lungmentioning
confidence: 81%
“…The specificity of binding may be imparted by the biologically active N terminus (ϳ40 aa in length), which is unique for each member of the annexin family (21). The N-terminal alanine of intact annexin I is acetylated and resistant to Edman degradation (8); the presence of the ⌬1-12 annexin I enabled identification of the sequence, though the intact form was also isolated (as found in immunoblots, not shown). In contrast, the S100A8/A9 complex present is exclusively in leukocytes (17,22) and probably originated from the trapped blood or sequestered neutrophils in bovine lung.…”
Section: Discussionmentioning
confidence: 99%
“…Other posttranslational modifications could include acetylation, sulfation, or glycosylation. NH 2 -terminal acetylation of ANXA1 has been suggested to regulate its interaction with cytoskeletal components such as the S100 calcium-binding family of proteins (15). Differences in N-linked glycosylation have also been shown to alter the charge characteristics of ANXA1, resulting in the generation of distinct isoforms that can be distinguished according to their pI (4).…”
Section: Discussionmentioning
confidence: 99%
“…This adduct ion has been observed by several authors and interpreted as a product of a reaction with nonpolymerized acrylamide during electrophoresis. Several authors (Chiari et al, 1992;Hall et al, 1993;Le Maire et al, 1993) reported the observation of acrylamidated cysteine residues. Klarskov et al (1994) found a peptide from an in-gel digestion with a mass increase of 71 Da, although the peptide did not contain cysteine.…”
Section: S Haebel Et Almentioning
confidence: 99%